Reformasi Tata Kelola Pemerintahan Desa melalui Penataan Kelembagaan (Studi di Desa Kubang Puji Kecamatan Pontang Kabupaten Serang) - Rachmi Yulianti (Sawala : Jurnal Administrasi Negara, 2018)
This paper is based on the condition of the Village Government Institutional Structure that was initially too fat, thus affecting the incapability of the village head to change the structure, norms, values and regulation of state personnel and cause the failure of efforts to fulfill the aspirations and needs of the community based on Law no. 6 Year 2014 Chapter III contains the Village Structuring which essentially wants to realize the effectiveness of the implementation of Village Government. The research method used in this research is descriptive qualitative method by using technique of Purpose Sampling then technique of field data collection by way of observation, depth interview, study of documentation and field research. The results of this study indicate that in institutional arrangement in Kubang Puji village, Pontang sub-district, there is a lot of involvement from the community so that the downsizing of Bureaucracy structure is influenced by people who have personal interest in the organization of the village so that there is a need for organizational structuring and improvement in the governance system, service and human resources management in accordance with the mandate of Law No. 6 of 2014.